Design, synthesis and herbicidal activity of novel quinazoline‐2, 4‐diones as 4‐hydroxyphenylpyruvate dioxygenase inhibitors. Issue 8 (29th September 2014) - Wang, Da‐Wei; Lin, Hong‐Yan; Cao, Run‐Jie; Ming, Ze‐Zhong; Chen, Tao; Hao, Ge‐Fei; Yang, Wen‐Chao; Yang, Guang‐Fu
Abstract BACKGROUND 4‐Hydroxyphenylpyruvate dioxygenase (HPPD) (EC 1.13.11.27) has been identified as one of the most promising target sites for herbicide discovery. To discover novel HPPD inhibitors with high herbicidal activity and improved crop selectivity, a series of novel triketone‐containing quinazoline‐2, 4‐dione derivatives possessing a variety of substituents at the N‐1 position of the quinazoline‐2, 4‐dione ring were designed and synthesised. RESULTS The results of in vitro tests and greenhouse experiments indicated that some analogues showed good HPPD inhibitory activity, with promising broad‐spectrum herbicidal activity at a rate of 150 g AI ha−1. Most surprisingly, compound 11 h, 1‐ethyl‐6‐(2‐hydroxy‐6‐oxocyclohex‐1‐enecarbonyl)‐3‐(o‐tolyl)quinazoline‐2, 4(1H, 3H)‐dione, showed the highest HPPD inhibition activity, with a Ki value of 0.005 μM, about 2 times more potent than mesotrione (Ki = 0.013 μM). Further greenhouse experiments indicated that compounds 11d and 11 h displayed strong and broad‐spectrum post‐emergent herbicidal activity even at a dosage as low as 37.5 g AI ha−1, which was superior to mesotrione. More importantly, compounds 11d and 11 h were safe for maize at a rate of 150 g AI ha−1, and compound 11d was safe for wheat as well. CONCLUSION The present work indicated that the triketone‐containing quinazoline‐2, 4‐dione motif could be a potential lead structure for further development of novel herbicides. © 2014 Society of Chemical Industry